2014
DOI: 10.1007/s10964-014-0171-2
|View full text |Cite
|
Sign up to set email alerts
|

Bicultural Stress, Identity Formation, and Alcohol Expectancies and Misuse in Hispanic Adolescents: A Developmental Approach

Abstract: Hispanic immigrant youth engage in increased health risk behaviors, such as alcohol misuse, due in part to being confronted with acculturative stress in addition to facing major normative developmental challenges, such as identity consolidation (Berry et al. in Appl Psychol 55:303-332, 2006). Using a developmental psychopathology framework, in the present study we examined the effect of bicultural stress on alcohol misuse among immigrated Hispanic adolescents, indirectly through trajectories of identity format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 67 publications
(81 reference statements)
2
37
0
1
Order By: Relevance
“…Some previous research, however, has suggested that the relation between stress and alcohol use may be different for boys and girls (Epstein, Botvin, & Diaz, 2000; Oshri et al, 2014). For Hispanic adolescents, less is known about the relation among stress, gender, and alcohol use.…”
Section: Discussionmentioning
confidence: 97%
“…Some previous research, however, has suggested that the relation between stress and alcohol use may be different for boys and girls (Epstein, Botvin, & Diaz, 2000; Oshri et al, 2014). For Hispanic adolescents, less is known about the relation among stress, gender, and alcohol use.…”
Section: Discussionmentioning
confidence: 97%
“…Confusion appears to represent a maladaptive sense of disorganization that is not necessarily the opposite of coherence but that predicts negative psychosocial and health outcomes. Indeed, there is evidence that a fragmented and confused sense of identity portends low self-esteem, internalizing symptoms, externalizing problems, and health risk behaviors among members of various ethnic groups (Oshri et al, 2014). Finally, while future studies are necessary to explore the directionality between personal and cultural identity across different development periods, as indicated by the stationarity results, these findings held across the first three waves of data, providing evidence for the generalizability of these findings over time.…”
Section: Discussionmentioning
confidence: 99%
“…Bicultural stress represents the cognitive appraisal of stress related to the conflict stemming from balancing two cultural streams simultaneously (Romero & Roberts, ). Most research on bicultural stress has focused on mental health outcomes (LaFromboise, Coleman, & Gerton, ; Love & Buriel, ; Romero, Carvajal, Valle, & Orduña, ; Wei et al., ), yet there is also some evidence that suggests a positive relationship between bicultural stress and frequency of alcohol and drug use (Oshri et al., ; Romero et al., ). However, these studies have either used U.S.‐born samples of Hispanic adolescents or have not examined the role of bicultural stress in conjunction with other cultural stressors—though more researchers are beginning to examine the combined influence of cultural stress (Cano et al., ; Schwartz et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental and social stressors can distract adolescents from developing their self‐identity (Szabo & Ward, ), but it is not clear whether cultural stressors impact identity formation among immigrant youth, and how these processes then impact cigarette or AOD attitudes. In adolescents, higher levels of identity confusion—or lower levels of identity coherence—may lead to an increased risk for experimentation with alcohol or drug use and other risky behaviors (Oshri et al., ; Schwartz et al., ).…”
Section: Introductionmentioning
confidence: 99%